(untitled) (Journal of the College of Basic Education, 2023)
Linguistic studies in the Holy Qur’an in general, syntax, morphology, and sound, and semantic research in particular, are still the subject of care and attention by scholars and researchers.Our scholars in the semantic (interpretive) field had the upper hand, the greatest credit, and the prominent impact in their codification and authoring many explanations, interpretations, and interpretations, in addition to that their sound opinions that were mentioned and disseminated in the books of interpretation.It must be pointed out that the Qur’an is distinguished by its brilliant and wonderful vocabulary, its pioneering (excellent) structures that are in harmony with each other, its eloquent style, and the splendor of its texts full of the most beautiful images of eloquence and the wonderful, and what they contain of renewed moral enrichment, in addition to that it is issued from a tongue that does not come to falsehood. before him or behind him,